EARLY MARRIAGE CONSTRUCTION AND PERPETUITY FACTORS IN DISCOURSE OF POWER AND RELIGION - M Khusnun Niam (BUANA GENDER : Jurnal Studi Gender dan Anak, 2021)
This article aims to describe and analyze the related construction of early marriages and the perpetuity factors in discourse of power and religion. Early marriage is one of the unhealthy phenomena and even causes high divorce, maternal mortality, and domestic violence rates. It becomes a warning from health experts. However, the lack of knowledge and the strong flow of normalization make early marriage one of the things recommended in a small number of regions, including Reban. In addition, this tradition is supported by an understanding of religion that contributes indirectly into paradigm through the paradigm. This research is a with a descriptive-analysis approach and Michel Foucault's power of knowledge. The data sources of this research were obtained from interviews and observations as primary sources, as well as books, journals, articles, and supporting data as secondary sources. The results of this research indicate that the construction of early marriages and perpetuity factors are mere normalization. There are a number of things that make this problem normalized including theological-normative contributions which are indirectly understood socially as well as the construction of power and knowledge about early marriage and its effects for people who experience it.